Meniscal Allograft Transplantation: Factors Predicting Failure. Issue 5 (31st May 2017) - Parkinson, Ben; Smith, Nicholas; Thompson, Peter; Spalding, Tim
Background: Meniscal allograft transplantation (MAT) has been shown to provide a significant improvement in patient reported outcomes for individuals with post-menisectomy syndrome. The typical patients undergoing MAT often have multiple other pathologies that require treatment at the time of surgery and it is difficult to ascertain which factors influence the outcome. Hypothesis / Purpose: The aim of this study was to determine the predictors of meniscal allograft transplantation failure in a large series in order to refine the indications for surgery and better inform future patients. Study Design: Prospective case series. Methods: All patients undergoing MAT at a single institution between May 2005 and May 2014, with a minimum of one year follow up were prospectively evaluated and included in this study. Failure was defined as removal of the allograft, revision transplantation or conversion to a joint replacement. Patients were grouped according to the articular cartilage status at the time of surgery; Group 1 – intact or partial thickness chondral loss; Group 2 - full thickness chondral loss one condyle; Group 3 - full thickness chondral loss both condyles. The Cox proportional hazards model was used to determine significant predictors of failure (cartilage grade at the time of MAT, IKDC score, lateral or medial allografts, gender, additional procedures and tissue bank source), independently of other factors. Kaplan-Meier survival curves were produced for overall survival and significant predictors of failure in the Cox proportional hazards model. Results: There were 125 consecutive MATs performed, with one patient lost to follow up. The median follow up was 3 years (range 1 – 10 years). The 5 year graft survival for the entire cohort was 82% (97% group 1, 82% group 2, 62% group 3). The probability of failure in group 1 was 85% lower (95% confidence interval 13 – 97%) than in group 3 at any time. The probability of failure with lateral allografts was 76% lower (95% confidence interval 16 – 89%) than medial allografts at any time. Conclusion: This study showed that the presence of severe cartilage damage at the time of MAT and medial allografts were significantly predictive of failure. Surgeons and patients can use this information when considering the risks and benefits of surgery.